PERENCANAAN DOUBLE TRACK LINTASAN KERETA API PADA EMPLASEMEN STASIUN MOJOKERTO - BOHARAN (KM 57+358 - KM 33+867) - Raynaldi Meidianto; Nugroho Utomo (Racic : Rab Construction Research, 2024)
Based on National Railway Master Plan (RIPNAS)in 2030, there is an increase in train passenger travel on Java Island by 858.5 million people/year. The capacity of the railway track is inadequate because it still uses a single track on the Mojokerto - Boharan line so that there is a plan for a double track railway. On Java Island, there are 2 railway routes, namely the northern route (pantura) and the southern route. For the northern route or the North Coast route connecting Jakarta and Surabaya, it is already a double track. While for the southern route in the form of a double track, it is still realized on the Jombang - Mojokerto track. Then, on the Mojokerto - Boharan track, the existing railway line is still a single track or single track. The main focus of this study is the planning of a double track railway at the placement of Mojokerto - Boharan Station (KM 53 + 400 - KM 51 + 700). The structure of the double track railway in the Mojokerto - Boharan section that was reviewed was the planning of a double track railway that was given a geotextile layer against the aspect of the planned railway load. The guidelines used in this design are the Regulation of the Service No. 10 of 1986 from PT. KAI. As a result of this study is a review of the safety factor due to dead load damage to the railway structure, the safety factor of slope and lateral swelling against the reinforcement of the geotextile layer meets the requirements.